Effect of tumour-cell-derived or recombinant keratinocyte growth factor (KGF) on proliferation and radioresponse of human epithelial tumour cells (HNSCC) and normal keratinocytes in vitro - Hille, Andrea (Springer-Verlag, 2010)
Purpose of this work was to test the effect of tumour-cell-derived keratinocyte growth factor (KGF) or recombinant KGF (palifermin) on cell proliferation and radiation response of human HNSCC cells and normal keratinocytes in vitro. Four tumour cell cultures derived from head and neck squamous cell carcinomas, primary keratinocytes, and immortalized keratinocytes were analysed. Fibroblasts, the natural source of KGF protein, served as controls. KGF expression was observed in primary and immortalized keratinocytes, fibroblasts, and in tumour cells, while significant KGF receptor expression was only found in keratinocytes. Recombinant KGF as well as tumour-cell-derived KGF caused a significant growth stimulation and radioprotection in keratinocytes, which was abolished by a neutralizing anti-KGF antibody. This indicates that tumour-cell-derived KGF is biologically active. In the tumour cell lines, no significant growth stimulation was induced by recombinant KGF, and the neutralizing antibody did not influence tumour cell growth or radiation response. Our results indicate that the normal, paracrine KGF regulatory mechanisms, which are based on KGF receptor expression, are lost in malignant cells, with the consequence of irresponsiveness of the tumour cells to exogenous KGF. In face of the amelioration of the radiation response of normal epithelia, demonstrated in various clinical and various preclinical animal studies, recombinant KGF represents a candidate for the selective protection of normal epithelia during radio(chemo) therapy of squamous cell carcinoma.